Ewaluacja programu profilaktyki wczesnego rodzicielstwa = Evaluation of an early parenthood prevention programme - Wąż, Krzysztof (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In Poland the prevention programmes concerning the risks of sexual activity are rarely implemented and evaluated. However, such projects which are related to sexual sphere and which interfere in the processes of psychosexual development require evaluation for substantive and ethical reasons. This article attempts to show a complex evaluation procedure which was used in the course of implementing into the Polish educational practice an early parenthood prevention programme based on the use of an electronic nursing simulator.
Keywords: parenthood; care; psychosexual development; prevention; rodzicielstwo; opieka; rozwój psychoseksualny; profilaktyka